Stress, Emotional Intelligence, and Health Management - Yadnya, I Dewa Gede Sayang Adi; Fadli, Fadli; Kusumawati, Prima Dewi; Ningsih, Eka Sarofah; Pudyastuti, Rita Rena (Poltekkes Kemenkes Palu, 2024)
Adolescents go through hormone, physical, psychological, and social changes that often cause emotional turmoil. The effects of emotional upheaval result in adolescents lacking the ability to control emotions, putting them at risk for stress. One of the factors that can minimize stress is emotional intelligence, which is a person's ability to manage emotions. The incidence of stress among adolescents in Central Java Province is 4.7%. Several things, namely problems in school, differences in arguments between parents and children, and relationships with peers, cause stress among adolescents. To know the relationship between emotional intelligence and the level of stress among adolescents in X High School. This research is a non-experimental quantitative research with a cross-sectional research design. Purposive sampling technique was used to select 85 students of X High School as the research participants. Kendall Tau was used to analyze data. There is a relationship between emotional intelligence and stress levels of adolescents at X High School. The results of the analysis with the Kendall tau test obtained p value = 0.000 means p value <0.05. The correlation coefficient or r value = 0.867 shows a very strong negative correlation. Conclusion: A highly significant negative relationship exists between Emotional Intelligence and stress.